Between animal research and animal welfare: Analysing the openness practices of UK Named Veterinary Surgeons - Renelle McGlacken; Pru Hobson-West (Animal Welfare, 2024)
The use of animals as scientific models is argued to be crucial for producing new scientific and medical knowledge and clinical treatments. However, animal research continues to raise socio-ethical concerns. In recent years, there has been a push for openness amongst the life science community, with the aim of increasing the transparency of animal research to wider publics. Yet, how this push for openness is experienced by those responsible for the care and welfare of research animals requires further study. This paper draws upon qualitative interviews with Named Veterinary Surgeons (NVS) in the UK and explores how they practise openness, avoid openness, and, at times, challenge the way their role is represented within openness agendas. Overall, this social scientific analysis reveals that the current openness agenda has the potential to create tensions for professionals, as they seek to manage regulatory and public imaginaries of the veterinary identity alongside the animal research controversy. The paper concludes by arguing for a culture of dialogue, where openness includes allowing those with responsibilities for animal welfare to express ambivalence or concern about their own role. Finally, the paper calls for sustained academic work on relations between the veterinary profession and wider society, particularly areas that involve contested practices in which care and harm may coincide.